Promoting Active and Effective Learning through the Student Teams-Achievement Divisions Model - Andini putri; subhanadri; Opi Andriani (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This research was motivated by the low achievement of the fourth-grade IPAS learning process and outcomes at SDN 128/II Pasir Putih. Initial observations conducted by the researcher, which revealed that only 38.46% of 26 students achieved a score that met the achievement criteria. The objective of this research is to improve the IPAS learning process and outcomes using the Student Teams Achievement Division model. The research consisted of two cycles. Each cycle consisted of two meetings, each consisting of four stages: planning, implementation, observation, and reflection. Data was collected through observation, tests, and documentation. Teacher observation results in cycle I has an average percentage of 85.42% and in cycle II has an average percentage of 91.67%, categorized as Very Good. The improvement in the learning process of students, in cycle I reached 76.92% in the category of quite good, and in cycle II increased to 92.31% in the category of very good. The increase in student learning outcomes in cycle I reached 65.38% in the category of sufficient, and cycle II reached 88.46% in the category of very good. 65.38 % is in the sufficient category, and cycle II reached 88.46% in the very good category. Based on the results it was found that the implementation of the STAD model can help students improve their learning comprehension skills.